(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The present paper overwies the issues of natural vegetation protection and preservation of the Reed bed and littoral zone geosystems that are in reservation conditions. The researches of the status of the herbaceous vegetation phytodiversity are made. It is established that rare species were loss of the herb stands, the plant cover and performance of edificators were sharp decreased due to the absolute conservation as a result of an excessive accumulation of mortmass in the composition of the swamp vegetation. The swampy-meadow coenosises as swampy, accumulated the significant amounts of mortmass and changed towards the formation of monospecies unproductive thinned communities. True-meadow coenosises increased productivity on the early stages, and further it were overgrown by shrub species. Salted-meadow communities in reservation conditions were changing by more mesophytic with a decrease in their species composition halophytic faction, in particular of a narrow ecological amplitude. The vegetation of overgrown sands in absolute reservation conditions accumulated significant amounts of mortmass and developed in the direction of forming meadow-steppe communities with domination of quitches gramen. Its phytomass was reduced and herbage was discharged. The valuable sod-forming cereals were disappeared. The synanthropic species distributed. On the basis of experimental researches on the removal of the part biomass, to preserve phytodiversity in areas that are outside of the areas of absolute conservation, it is proposed the regulated grazing, mowing, and in some cases - burning grass.